The xenarthrans of Honduras: new records, main threats, and comments on their conservation status - Turcios Casco, Manfredo A. (2020)
The Xenarthra are one of the least studied mammalian groups in Honduras. Their ecology, natural history, and distribution in the country are poorly known. Here we compile and discuss, for the first time, the available information about the seven species of Xenarthra that occur in Honduras. We also present new distribution records and comment on their main threats. The lack of specific scientific studies, poaching, illegal traffic, cultural beliefs, and deforestation are among the main threats to xenarthrans in Honduras.